2009
DOI: 10.1139/o08-147
|View full text |Cite
|
Sign up to set email alerts
|

A glycosylated antitumor ether lipid kills cells via paraptosis-like cell death

Abstract: Glycosylated antitumor ether lipids (GAELs) have superior anticancer properties relative to the alkyllysophospholipid class, but there have been no studies of the mechanisms of these compounds. The prototype GAEL, 1-O-hexadecyl-2-O-methyl-3-O-(2'-amino-2'-deoxy-beta-D-glucopyranosyl)-sn-glycerol (Gln), effectively killed mouse embryonic fibroblasts (MEFs) lacking key molecules involved in caspase-dependent apoptosis, and cell death was not prevented by caspase inhibitors. Gln did not cause a loss of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 36 publications
2
50
0
Order By: Relevance
“…Here we have shown with a range of assays, including of LC3-II synthesis studies (in the presence of bafilomycin A1), studies with GFP-RFP-LC3, and assays of both endogenous and exogenous autophagy substrate accumulation/degradation, that Gln primarily acts to decrease autophagic flux by impairing lysosomal acidification. However, our data showing that Gln-induced cell death is independent of autophagy and caspases are compatible with those of Sammader et al 26 Here, we have advanced the understanding of the cell death mechanism by revealing that this is due to leakage of cathepsins from lysosomes. Thus, this cell death is independent of autophagy and caspases, but appears to be due to leakage of cathepsins from lysosomes.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Here we have shown with a range of assays, including of LC3-II synthesis studies (in the presence of bafilomycin A1), studies with GFP-RFP-LC3, and assays of both endogenous and exogenous autophagy substrate accumulation/degradation, that Gln primarily acts to decrease autophagic flux by impairing lysosomal acidification. However, our data showing that Gln-induced cell death is independent of autophagy and caspases are compatible with those of Sammader et al 26 Here, we have advanced the understanding of the cell death mechanism by revealing that this is due to leakage of cathepsins from lysosomes. Thus, this cell death is independent of autophagy and caspases, but appears to be due to leakage of cathepsins from lysosomes.…”
Section: Resultssupporting
confidence: 91%
“…26 Indeed, this situation has some similarities to what was previously noted by Overmeyer et al 29 and represents a form of cell death mediated by lysosomes. 30 It has been previously suggested that some lysosomotropic amines can act as detergents, once they reach a high enough concentration in the lysosomes.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations